Medieval Glosses as a Test Subject for the Building of Tools for Digital Critical Editions - Emmanuelle Kuhry (Journal of the Text Encoding Initiative)
The thirteenth-century Latin corpus of the Oxford gloss has challenging features. A digital scholarly edition of this corpus necessitates innovative solutions that on the one hand account for the complex structure and content of the text and its manuscript transmission, and on the other hand convey these data comprehensibly to the reader. There are still few user-friendly tools which allow scholars to encode a digital critical edition easily, particularly its critical apparatus, in TEI XML. In this article, I document my approach to editing a digital corpus of philosophical glosses, and explain the tools I am using and customizing to make available to a larger public of digital scholarly editors, especially in the field of medieval studies.